'Surfaces-as-ligands, surfaces-as-complexes' strategies for copper(I) dye-sensitized solar cells. (April 2015) - Schönhofer, Ewald; Bozic-Weber, Biljana; Martin, Colin J.; Constable, Edwin C.; Housecroft, Catherine E.; Zampese, Jennifer A.
Abstract: A series of TiO2 -supported copper(I) dyes, [Cu(Lanchor ) (Lancillary )] + with Lancillary = 2, 2′:4′, 4″:2″, 2‴-quaterpyridine (1 ), 4, 4′-bis(6-methyl-[2, 2′-bipyridin]-4-yl)-1, 1′-biphenyl (2 ), or 4, 4′-bis(6, 6′-dimethyl-[2, 2′-bipyridin]-4-yl)-1, 1′-biphenyl (3 ), and Lanchor = (6, 6′-dimethyl-[2, 2′-bipyridine]-4, 4′-diyl)bis(4, 1-phenylene)bis(phosphonic acid) (4 ), has been assembled in a stepwise manner. DSSCs incorporating these dyes demonstrate the need for 6, 6′-substituents in both ligands in [Cu(Lanchor ) (Lancillary )] + ; both J SC and V OC increase on going from [Cu(4 ) (1 )] + to [Cu(4 ) (2 )] + to [Cu(4 ) (3 )] + . First, second and third generation dyes [(4 )Cu(3 )n ] n+ (n = 1, 2 or 3) have been assembled using the 'surfaces-as-ligands, surfaces-as-complexes' strategy, although the separation between sites of electron injection and hole transporting domains in the multinuclear complexes fails to enhance DSSC performance. Replacing Lancillary 2 in [Cu(4 ) (2 )] + by the metalloligand Ru(bpy)2 (2 ) 2+ improves dye performance due to the better spectral response of the heteronuclear [Cu(4 )(2 )Ru(bpy)2 ] 3+ complex. This assembly approach presents a flexible method of tuning dye properties while retaining the surface-bound bis(diimine)copper(I) domain. Graphical abstract: First, second and third generation TiO2 -anchored copper(I) dyes [(Lanchor )Cu(Lancillary )n ] n+ (n = 1, 2 or 3) in which Lancillary is a ditopic bis(2, 2′-bipyridine) domain and Lanchor contains 2, 2′-bipyridine and phosphonic acid domains have been assembled using a versatile 'surfaces-as-ligands, surfaces-as-complexes' strategy. We demonstrate that 6, 6′-substituents are required in both ligands in first-generation [Cu(Lanchor ) (Lancillary )] + to enhance J SC and V OC values. Replacing Lancillary by a metalloligand Ru(bpy)2 (Lancillary ) 2+ improves dye performance due to the better spectral response of the heterometallic [(Lanchor )Cu(Lancillary )Ru(bpy)2 ] 3+ complex. Highlights: Stepwise assembly of anchored dyes in n-type DSSCs. 'Surfaces-as-ligands, surfaces-as-complexes' dye assembly. Atom efficient dye assembly strategies to construct homometallic or heterometallic dyes. On-surface strategies for dye assembly on n-type semiconductor surfaces.